The Effect of Combination of Green Tea and Roselle Extract on Morphology and Motility of Spermatozoa in Rats Induced by Monosodium Glutamate - Nurjaya Adinugroho; Awal Prasetyo; Eriawan Agung Nugroho (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Infertility is a reproductive system problem and has been increasing recently. One of the reasons is the poor quality of spermatozoa, which can be assessed through its morphology and motility. Excessive consumption of MSG can affect the quality of spermatozoa. The provision of a combination of green tea and roselle extract, which is an antioxidant and is expected to be able to counteract the effects of MSG’s free radicals on spermatozoa. The objective of the study is to determine the morphology and motility of Wistar Rats’ spermatozoa in the control group given MSG and in the experimental group given MSG and a combination of green tea and roselle extract at a dose of 200 mg/kg/day and 400 mg/kg/day for 14 days. Methods: Fifteen Wistar rats were randomly divided into three groups, a control group with MSG, group 1 with MSG and a combination of green tea and roselle extract at a dose of 200 mg/kg BW/day (P1), and group 2 with MSG and combination green tea and roselle extract at a dose of 400 mg/kg BW/day (P2). After 14 days of treatment, the morphology and motility of the spermatozoa of each mouse were studied and assessed microscopically. Results: In the morphological study, the control group had the lowest normal value and the highest abnormal value among all groups. Meanwhile, the P1 group had the highest normal and lowest abnormal values compared to the other two groups. Conclusion: The administration of a combination of green tea and roselle extract improved the morphology and motility of Wistar rats’ spermatozoa. However, an increased dose of a combination of green tea and roselle extract was not proven to affect the morphology and motility of Wistar rats' spermatozoa.